THE REFLECTION OF HIGH RENAISSANCE AND MANNERISM OF THE WORKS OF MICHELANGELO BUONARROTI IN THE INTERPRETATION OF IRVING STONE IN HIS LAST BIOGRAPHICAL NOVEL THE AGONY AND THE ECSTASY - Kwiatkowska, Anna (Acta Neophilologica, 2013)
The article focuses on the artistic elements of Italian High Renaissance and Mannerism in the narrative structure of the biographical novel about Michelangelo Buonarroti, The Agony and the Ecstasy, by Irving Stone. The discussion of the above is limited to one selected aspect of narration, namely a description. The analysis includes ekphrastic passages referring to the most well known, monumental sculptural pieces by Michelangelo Buonarroti. The aim of the article is to establish the extend to which the literary descriptions form the novel by Irving Stone reflect the character and style of the 16th century sculptures of Michelangelo.